Exchange rate policy and regional trade agreements: A case of conflicted interests? - Richard Pomfret; Victor Pontines (Asian Development Bank Institute (ADBI), 2013)
The results highlight the conflicting interests of countries - to stabilize exchange rates or to keep the option of exchange rate depreciation in order to maintain competitiveness of domestic tradable producers. With deepening integration in East Asia, however, the desire for exchange rate stability will eventually outweigh the desire to maintain a protectionist tool. How extensive the pressures will be in East Asia will depend not only on how many countries seriously desire to be in the more integrated economic area in which Factory Asia operates, but also on their institutional and political readiness to commit in such schemes at the cost of renouncing an important policy instrument.
Keywords: F13; F14; F15; F42; 330; regional trade agreement; exchange rate depreciation; exchange rate stability; asean+3; Wechselkurspolitik; Internationaler Wettbewerb; Handelsabkommen; Ostasien